Cutaneous noradrenaline measured by microdialysis in complex regional pain syndrome during whole-body cooling and heating - Terkelsen, Astrid J.; Gierthmühlen, Janne; Petersen, Lars J.; Knudsen, Lone; Christensen, Niels J.; Kehr, Jan; Yoshitake, Takashi; Madsen, Caspar S.; Wasner, Gunnar; Baron, Ralf; Jensen, Troels S. (Experimental neurology, 2013)
Complex regional pain syndrome (CRPS) is characterised by autonomic, sensory, and motor disturbances. The underlying mechanisms of the autonomic changes in CPRS are unknown. However, it has been postulated that sympathetic inhibition in the acute phase with locally reduced levels of noradrenaline is followed by an up-regulation of alpha-adrenoceptors in chronic CRPS leading to denervation supersensitivity to catecholamines. This exploratory study examined the effect of cutaneous sympathetic activation and inhibition on cutaneous noradrenaline release, vascular reactivity, and pain in CRPS patients and in healthy volunteers. Seven patients and nine controls completed whole-body cooling (sympathetic activation) and heating (sympathetic inhibition) induced by a whole-body thermal suit with simultaneous measurement of the skin temperature, skin blood flow, and release of dermal noradrenaline. CRPS pain and the perceived skin temperature were measured every 5min during thermal exposure, while noradrenaline was determined from cutaneous microdialysate collected every 20min throughout the study period. Cooling induced peripheral sympathetic activation in patients and controls with significant increases in dermal noradrenaline, vasoconstriction, and reduction in skin temperature. The main findings were that the noradrenaline response did not differ between patients and controls or between the CRPS hand and the contralateral unaffected hand, suggesting that the evoked noradrenaline release from the cutaneous sympathetic postganglionic fibres is preserved in chronic CRPS patients. ► Complex regional pain syndrome (CRPS) is characterised by autonomic disturbances. ► Is local noradrenaline (NE) release preserved in the zone of evoked pain? ► The sympathetic nervous system was modulated by whole-body cooling and heating. ► For all patients, the pain intensity during cooling was higher than during baseline. ► NE release from cutaneous sympathetic postganglionic fibres in chronic CRPS was preserved.